EBT3 Films in Low Solar Ultraviolet and X-Ray Dose Measurement: A Comparative Analysis - Saleh K. Alsaee; Ahmad Fairuz Omar; Naser M. Ahmed; Ahmed Alsadig; A. Sulieman; Khalid Alzimami (SAGE Publishing, 2019)
The purpose of this study is to investigate the potentiality of Gafchromic external beam therapy 3 (EBT3) film to measure low dosage of solar ultraviolet (SUV; 0-10 600 mJ/cm 2 ) and x-ray (0-750 mGy) radiation. In this experiment, 2 groups of EBT3 films were prepared with size 2 cm × 1 cm. The first group of films was exposed by incremental SUV dose in the middle of the day. The other group was irradiated by x-ray at 100 kVp, 100 mA, and 2 S of tube voltage, tube current, and exposure time, respectively. The measured SUV consists of 90% ultraviolet A (UVA) and 10% ultraviolet B. The film discoloration was represented by visible absorbance spectroscopy technique using Jaz spectrometer from Ocean Optics Inc. Simple linear regression produced high accuracy with coefficients of determination, r 2 of 0.9804 and root mean square error (RMSE) of 434.88 mJ/cm 2 for the measurement of SUV dose. On the other hand, r 2 of 0.98 and RMSE of 31 mGy was produced for the measurement of x-ray dose. The application of multiple linear regression enhanced the measurement accuracy with R 2 of 99% and 99.7% and RMSE of 327.06 mJ/cm 2 and 15.045 mGy for SUV and x-ray dose, respectively. The spectral analysis shows a promising measurement at selected wavelengths for SUV and x-ray dose.